Implementasi Java RMI pada Rancang Bangun Tes Toefl Online Berbasis Web - Sri Lestari; Maman Somantri; R. Rizal Isnanto (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
The advances in information technology today has sparked growth in the number of Internet users. Ease of accessing the internet makes it the best way of presenting data for both individuals and institutions. Similarly UNDIP who have harnessed the Internet to present information such as presenting transcripts of students, teachers’ and students’ data, etc. However, for organizing the job vacancies to graduates and students, UNDIP is still using the faculty information systems respectively. A better way to facilitate access to the job vacancies is to design an information system that records and organizes all of the job vacancies to students and graduates of UNDIP. Design and implementation will begin with a system requirements analysis which is intended to obtain an appropriate system specifications. Within the design stage, Data Flow Diagram will be used to provide a clear representation of any business function, meanwhile ERD will be used to provide a logical representation of data in this system. The design is then implemented with the PHP programming language and MySQL database and also the addition of java script to create a more dynamic Web. The results of implementation and system testing show that system is running properly and in accordance with the system specifications, particularly system’s e-mail and SMS notification for newly inputted job vacancies that meet jobseekers’ specifications. Keyword : web-based information system, PHP, MySQL